Integrating technology acceptance, social information, and social cognitive theory in an e-Dakwah framework for Indonesia - Prabowo, Nugroho Agung (2025)
The e-Dakwah framework that has been used in Indonesia still shows fundamental weaknesses, especially in the integration of technological, social, and religious values. Most of the existing models have not been able to bridge the complexity of the needs of Muslim users in the digital context, resulting in the low adoption rate and effectiveness of Islamic da'wah delivery through electronic media. The absence of an integrated mechanism in the delivery of socio-religious information that can influence behavior is the main problem underlying this study. This research aims to design and develop an e-Dakwah framework that integrates Technology Acceptance Model (TAM), Social Information (SI), and Social Cognitive Theory (SCT) as theoretical and practical solutions to these shortcomings. This study uses a quantitative and qualitative approach through the stages of systematic literature review, Focus Group Discussion (FGD), expert validation, and model testing through Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). Additional validation was carried out with System Usability Scale (SUS) instruments and expert assessments to measure the feasibility and usability of the system. The results of the study show that the integration of nine main variables including Perceived Ease of Use, Perceived Usefulness, Attitude Toward Use, Behavioral Intention, Actual Use, Social Influence, Content, Platform, and Infrastructure can form a more contextual, adaptive, and applicative framework in supporting the success of e-Dakwah. This model not only increases the acceptance of digital da'wah technology but also reflects relevant local religious and cultural values in Indonesia's Muslim society. The main contribution of this research lies in the development of an original theoretical framework, with a multidisciplinary approach that bridges the theory of technology adoption with socio-religious dynamics. The implications of this research are very significant, both for the development of a more inclusive and sustainable e-Dakwah system, as well as an academic and practical reference in the development of community-based religious technology in the digital era.